570. INCIDENCE AND ONCOLOGICAL IMPLICATION OF ADRENAL INCIDENTALOMAS IN ESOPHAGEAL CANCER PATIENTS. (24th September 2022) - Van Doesburg, Jasmijn; Voeten, Daan; Kalff, Marianne; Jol, Saskia; van der Bergh, Janneke; Engelsman, Anton; Gisbertz, Suzanne; Daams, Freek
Abstract: Adrenal incidentalomas are regularly encountered during imaging for esophageal cancer patients, but their oncological significance remains unknown. This study aimed to describe the incidence and etiology of adrenal incidentalomas observed during the diagnostic workup for esophageal cancer. This retrospective cohort study included all esophageal cancer patients referred to or diagnosed in the Amsterdam UMC between January 2012 and December 2016. Radiology and multidisciplinary team meeting reports were reviewed for adrenal incidentalomas. In case of adrenal incidentaloma, the 18FDG-PET/CT was reassessed by a radiologist blinded for the original report. In case of a metachronous incidentaloma during follow-up, visibility on previous imaging was reassessed. Primary outcome was the incidence, etiology and oncological consequence of synchronous adrenal incidentalomas. This study included 1, 164 esophageal cancer patients, with a median age of 66 years. Patients were predominantly male (76.1%) and most had an adenocarcinoma (69.0%). Adrenal incidentalomas were documented in 138 patients (11.9%) during the diagnostic workup. At primary esophageal cancer workup, 22 incidentalomas proved malignant. However, follow-up showed seven malignant incidentalomas missed or inaccurately diagnosed as benign. In total, stage migration occurred in 15 of 22 (68.2%), but this number would have been higher if no incidentalomas were missed or inaccurately diagnosed. The oncological impact of adrenal incidentalomas in patients with esophageal cancer is significant as a considerable part of incidentalomas changed treatment intent from curative to palliative. As stage migration is likely, pathological examination of a synchronous adrenal incidentaloma should be considered.